School Constraints in Recruitment and Implementation of Industrial Classes - Wika Forestyanto, Yoga Wika Forestyanto; Syamwil, Rodia; Wijaya, M. Burhan Rubai (Journal of Vocational and Career Education, 2019)
Industrial Class is a cooperation class between school and industry with the aim that graduates can directly be accepted to work in industry. In addition to its industry-based curriculum, this class receives support from industry in the management of learning and instructors from industry, as well as internship opportunities with special facilities in industry. The advantage of the school is the absorption of graduates with relatively short waiting periods or no waiting periods for graduates. The purpose of this study is to analyze the constraints of the recruitment process and the implementation of Industrial Classes in schools. This study used a qualitative method. The information used is manager and industrial class teacher. Data sources used are the principal and the Industrial Human Resource Development (HRD). The research instrument was an interview sheet. The data analysis of this research were data collection, data reduction, data presentation, and drawing conclusions. The population of this study was the Vocational High School in Semarang with samples of state vocational school 1 Semarang, State vocational school 11 Semarang, and central java state vocational school. The results showed that the implementation of the Industrial Class still had several problems, including (1) schools found it difficult to collaborate with industry; (2) there is no ideal industrial class recruitment model reference yet; (3) Industrial Class socialization is very limited and has not been able to capture qualified prospective students; (4) new students (VHS) do not yet know information related to industry; (5) parents and the community still consider negatively at vocational education that is identical with violence, delinquency, and difficulty in getting a job; (6) industrial involvement is still limited or not optimal; (7) there is no guarantee that students who graduate from Industrial Class will be accepted to work in the industry; (8) schools find it difficult to collaborate with industry; and (9) Schools lack competent leaders.